1998
DOI: 10.1016/s0886-3350(98)80108-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens calculator for childhood cataract

Abstract: If pseudophakia and aphakia have the same effect on the growth of the eye, this program should accurately predict the myopic shift of a pseudophakic child. This could help guide the surgeon's choice of IOL power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…The appropriate postoperative target refraction is also unclear. 5,6,15 In their retrospective study of 101 consecutive pediatric patients undergoing cataract extraction (median age, 4.8 years), Neely et al 16 found that only 61% of patients 24 months and younger had a refractive result within 2 D of their postoperative target using SRK II, SRK T, Holladay, and Hoffer Q formulas. A review of their data shows lens calculation errors up to 10 D at axial lengths Ͻ18 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate postoperative target refraction is also unclear. 5,6,15 In their retrospective study of 101 consecutive pediatric patients undergoing cataract extraction (median age, 4.8 years), Neely et al 16 found that only 61% of patients 24 months and younger had a refractive result within 2 D of their postoperative target using SRK II, SRK T, Holladay, and Hoffer Q formulas. A review of their data shows lens calculation errors up to 10 D at axial lengths Ͻ18 mm.…”
Section: Discussionmentioning
confidence: 99%
“…O uso de lentes intra-oculares em crianças vem se tornando cada vez mais comum, resultando numa correção da hipermetropia de forma constante e duradoura (10,22) . Em relação ao poder da lente a ser implantada em crianças, dois raciocínios podem ser usados: o implante de uma lente com objetivo de emetropização no pós-operatório imediato ou produzir um erro refrativo inicial de hipermetropia, considerando-se que ocorrerá uma diminuição desta hipermetropia ao longo do pós-operatório (11)(12)14,(23)(24) . Alguns autores preconizam um desconto de 6 dioptrias do poder dióptrico da lente calculada para emetropia em olhos operados entre 4 e 8 semanas e de 3 dioptrias em crianças de 1 a 4 anos de idade.…”
Section: Discussionunclassified
“…Com o advento das lentes de câmara posterior, o índice de complicações foi bem inferior e o seu uso na correção da afacia em crianças foi mais aceitável (9)(10) . Uma das mais cruciais perguntas referente ao implante da lente intra-ocular é o poder dióptrico da lente a ser implantada (9,11) . Alguns autores preconizam o implante de uma lente com valor dióptrico calculado para emetropia na ocasião da cirurgia (12) ou hipocorrigir com o objetivo de antecipar as mudanças do valor biométrico devido ao crescimento axial do globo ocular (13)(14)(15)(16) .…”
unclassified
“…Previous retrospective studies have shown the myopic shift as well as the error range in IOL power calculation in children [7, 8,11,12,13,14,15,16,17,18]. To reduce the necessity of IOL exchange, these eyes may be undercorrected, with the residual refractive error corrected by spectacles that are adjusted throughout life according to the refractive development.…”
Section: Introductionmentioning
confidence: 99%